PENYULUHAN HUKUM TENTANG PERLINDUNGAN DATA PRIBADI DI LINGKUNGAN YAYASAN SYAHRON BADAWI KOTA BATAM - Miftahul Huda; Lenny Husna; Diki Zukriadi; Padrisan Jamba (ASOSIASI IDEBAHASA KEPRI, 2026)
The increasing use of digital technology in educational and social institutions has raised significant concerns regarding the protection of personal data. Yayasan Syahron Badawi, located in Sagulung District, Batam City, manages various categories of personal data belonging to administrators, educators, students, parents, employees, and donors. However, preliminary observations indicated that the foundation's administrators had limited understanding of the legal principles governing personal data protection as stipulated in Law Number 27 of 2022 concerning Personal Data Protection. This community service program aimed to enhance the legal awareness and competence of foundation administrators in managing personal data securely and in compliance with applicable regulations. The program employed a participatory approach through legal counseling, interactive discussions, case studies, and practical assistance. The activities focused on introducing the fundamental principles of personal data protection, the rights of data subjects, the obligations of data controllers, and preventive measures to mitigate the risks of data misuse and breaches. The implementation of the program improved participants' understanding of legal responsibilities and encouraged the adoption of safer and more accountable data management practices within the foundation. This initiative demonstrates that legal counseling is an effective strategy for strengthening legal awareness and promoting sustainable personal data governance in community-based institutions.